2015
DOI: 10.17268/sci.agropecu.2015.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of classic stereotypies in endurance horses

Abstract: Resumen El objetivo del estudio fue determinar la frecuencia de estereotipias clásicas en caballos de enduro de la Región Metropolitana (Chile) y la asociación de estas conducta anormales con la edad y sexo de los animales. Se estudió la totalidad de los caballos de enduro residentes en 8 centros ecuestres de la Región Metopolitana (n=107). A cada cuidador se le describió las estereotipias clásicas (aerofagia, balanceo y paseo circular en pesebrera) y luego se le consultó por su presencia-ausencia en los equin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
0
0
Order By: Relevance
“…In our sample, lack of social interaction is common. The prevalence of stereotypic behaviour, we found, is in line with findings of previous studies on sport and leisure horses (Kennedy et al, 1993;McGreevy et al, 1995b;Muñoz-Alonzo et al, 2015). For example, McGreevy et al (1995b) reported that the prevalence of stereotypies for dressage, eventing and endurance horses ranged from 19.5% to 32.5% and found that the time a horse spends out of the stable is negatively correlated with an increased risk of abnormal behaviour.…”
Section: Discussionsupporting
confidence: 91%
“…In our sample, lack of social interaction is common. The prevalence of stereotypic behaviour, we found, is in line with findings of previous studies on sport and leisure horses (Kennedy et al, 1993;McGreevy et al, 1995b;Muñoz-Alonzo et al, 2015). For example, McGreevy et al (1995b) reported that the prevalence of stereotypies for dressage, eventing and endurance horses ranged from 19.5% to 32.5% and found that the time a horse spends out of the stable is negatively correlated with an increased risk of abnormal behaviour.…”
Section: Discussionsupporting
confidence: 91%
“…Zu hohen Ergebnissen kommt auch das Forscherteam von Muñoz-Alonzo et al (2015), welches 107 Distanzpferde aus acht Reitställen untersuchte und bei 12,2 Prozent Stereotypien wie Koppen, Weben und Boxenlaufen feststellte (vgl. Muñoz-Alonzo et al, 2015, S. 119-124).…”
Section: Definition Und Analogien Zum Menschenunclassified